Quality of public health services received by immigrant labours: a case study in Klang Valley - Normah Awang, Noh; Haris Abdul Wahab,; Siti Hajar Abu Bakar Ah, (penerbit ukm, 2014)
Quality is the most important element in the process of production or services produced by organization to its customers. Quality of service refers to the measure of how a service is delivered matches customer expectations. The study aims to examine the quality of public health services received by immigrant labours. There are three aspects of quality in public health services to be measured i.e health service condition, the waiting time for treatment and treatment by hospital staff on immigrant labours. The result showed a large number of immigrant labours are satisfi ed with the quality of health services.